Preparation process and application of chemical flocculant for textile printing and dyeing wastewater treatment

By preparing flocculants that combine chitosan and starch with aluminum salt and iron salt, the residual and environmental safety problems of traditional flocculants are solved, and the efficient removal of suspended substances and difficult-to-degrade organic matter in textile printing and dyeing wastewater is achieved, and the treatment efficiency and environmental protection are improved. sex.

CN119161004APending Publication Date: 2024-12-20MIANYANG GANLION PRINTING & DYEING +1

Patent Information

Application Number
CN202411301819.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In traditional textile printing and dyeing wastewater treatment, chemical flocculants such as aluminum salts and polyacrylamides have residual and environmental safety threats during use, making it difficult to effectively remove high color and difficult to degrade organic pollution.

Method used

Chitosan and starch are used as the main raw materials, combined with aluminum salt and iron salt, citric acid and lactic acid are added, and powdered flocculants with particle sizes of 20-80 microns are prepared through specific dissolution, purification, drying and pulverization processes, and Mixed with partially hydrolyzed polyacrylamide additive to form a stable flocculant.

Benefits of technology

It significantly improves the activity and stability of the flocculant, can efficiently remove suspended substances and organic pollutants in wastewater, reduces the risk of secondary pollution of chemical agents, and improves treatment efficiency and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161004A_ABST
    Figure CN119161004A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process and application of a chemical flocculant for textile printing and dyeing wastewater treatment, and the preparation process comprises the following steps: selecting chitosan and starch as main raw materials, modifying the starch through oxidation treatment or cationization treatment, and combining aluminum salt, ferric salt, citric acid and lactic acid according to a specific ratio, so as to obtain the chemical flocculant for textile printing and dyeing wastewater treatment. Synthesizing a stable composite material under the condition of controlling the temperature and the pH value; the preparation method comprises the following steps: preparing a composite material, drying the composite material, crushing the dried composite material into a powdery flocculating agent with uniform particle size, and finally mixing the powdery flocculating agent with a polyacrylamide auxiliary agent to prepare the efficient flocculating agent. The method is suitable for treating wastewater with high chroma and refractory organic matters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, in particular to a preparation process and application of a chemical flocculant for treating textile printing and dyeing wastewater. Background Art

[0002] A large amount of wastewater generated during the production process of the textile printing and dyeing industry contains complex organic matter, inorganic salts, various dyes, auxiliaries and other chemical substances. These wastewaters usually have the characteristics of high chroma, high chemical oxygen demand (COD), high biological oxygen demand (BOD), high salt content and unstable pH value. At the same time, some dyes and auxiliaries in printing and dyeing wastewater are difficult to be completely degraded in the natural environment due to their complex structure, large molecular weight and stable chemical properties, thus causing serious pollution to the ecological environment and water resources;

[0003] At present, the treatment methods of textile printing and dyeing wastewater mainly include three categories: physical method, chemical method and biological method. Physical methods such as sedimentation and filtration are mainly used to remove suspended matter in wastewater, but the removal effect on soluble organic pollutants and color is limited; chemical methods mainly include chemical oxidation, reduction, electrolysis and flocculation precipitation, etc. Although they have a certain removal effect on organic matter and color, there are problems such as high treatment cost, large amount of chemical use, and secondary pollution; biological methods such as activated sludge method and anaerobic digestion method usually have a good treatment effect on biodegradable organic matter, but the removal effect on difficult-to-degrade dyes and auxiliaries is poor, and the treatment cycle is long;

[0004] Among the above treatment methods, chemical flocculation is widely used in the pretreatment and deep treatment of textile printing and dyeing wastewater due to its simple equipment, convenient operation and significant treatment effect. Flocculants neutralize the charge of colloidal particles in wastewater and enhance the aggregation between particles, thereby forming larger flocs that are easy to precipitate and separate;

[0005] However, traditional chemical flocculants, such as inorganic flocculants such as aluminum salts and iron salts and organic polymer flocculants such as polyacrylamide, bring some problems during use. First, aluminum salt flocculants easily form residual aluminum ions in water, and long-term drinking of water containing aluminum ions will have adverse effects on human health; second, polyacrylamide flocculants may release toxic acrylamide monomers during the degradation process, posing a threat to the environment and biological safety.

[0006] Based on this, a preparation process and application of a chemical flocculant for treating textile printing and dyeing wastewater is needed. Summary of the invention

[0007] To achieve the above object, the present invention provides the following scheme: a preparation process of a chemical flocculant for treating textile printing and dyeing wastewater, the preparation process comprising the following steps:

[0008] S1, chitosan and starch are selected as main raw materials, the mass ratio of chitosan to starch is 1:1 to 1:3, and inorganic salts such as aluminum salt and iron salt are added, the mass ratio of aluminum salt to iron salt is 1:1 to 1:2, and citric acid and lactic acid are added as organic acid substances, the mass ratio of citric acid to lactic acid is 1:1 to 2:1;

[0009] S2, dissolving chitosan and starch at 30° C. to 50° C. for 1 to 3 hours, and then purifying them, dissolving aluminum salt and iron salt in deionized water to prepare 0.05M to 0.1M solutions, and dissolving citric acid and lactic acid to prepare 0.1M to 0.2M solutions for later use;

[0010] S3, gradually adding the purified chitosan solution to the mixed solution of aluminum salt and iron salt under stirring, controlling the reaction temperature at 40°C to 60°C, and the pH value at 4 to 6, adjusting the pH value by adding citric acid and lactic acid solution, and maintaining stirring reaction for 1 to 3 hours to form a stable composite material;

[0011] S4. Dry the synthesized composite material at 50°C to 70°C for 3 to 5 hours, and then grind it to obtain a powdered flocculant with a particle size of 20 to 80 microns. Finally, evenly mix the powdered flocculant with a polyacrylamide additive whose mass accounts for 1% to 10% of the total mass of the powdered flocculant to prepare a flocculant.

[0012] Furthermore, the deacetylation degree of the chitosan is in the range of 70% to 90%. During the raw material pretreatment process, the chitosan is dissolved in an acetic acid solution, the concentration of the acetic acid solution is 0.1M to 0.5M, the dissolution temperature is controlled between 40°C and 50°C, and the dissolution time is 2 to 4 hours. After the chitosan solution is dissolved, it needs to be filtered to remove insoluble impurities. A continuous stirring method is adopted with a stirring speed of 100 to 300 rpm to promote the complete dissolution of the chitosan. After the solution is dissolved, the solution is cooled to room temperature and left to stand for 24 hours to improve the stability of the solution.

[0013] Furthermore, the starch is an oxidized starch that has been oxidized or a cationic starch that has been cationized. During the raw material selection process, the starch is treated with a 30% to 40% hydrogen peroxide solution at 60°C to 70°C for 1 to 2 hours to introduce carboxyl groups or hydroxyl groups to enhance its hydrophilicity and reactivity. The treated starch solution is washed, filtered and dried, and then a sodium hydroxide solution is added to adjust the pH value to between 6.5 and 7.5, and then dissolved in deionized water for final mixing with chitosan.

[0014] Furthermore, the inorganic salts are aluminum sulfate and ferric chloride. During the preparation of the inorganic salts, aluminum sulfate and ferric chloride are mixed in a mass ratio of 1:1 to 1:2, and dissolved in deionized water with a concentration of 0.05M to 0.1M, respectively. The stirring time is controlled at 30 to 60 minutes at 40°C to 60°C, and then the two inorganic salt solutions are mixed and stirred for 20 to 30 minutes to form a uniform mixed solution. The pH value of the mixed solution is then adjusted to between 5.0 and 5.5 using a solution pH regulator, and this pH value is maintained until mixed with chitosan and starch.

[0015] Furthermore, in the synthesis step of the composite material, the chitosan solution is slowly added to the mixed solution of aluminum salt and iron salt, the stirring speed is maintained at 200 to 400 rpm during the mixing process, and the addition rate is controlled to 2 to 5 ml per minute, the reaction temperature is controlled between 50°C and 60°C, and the reaction solution is continued to be stirred for 30 to 60 minutes after the reaction is completed.

[0016] Furthermore, vacuum drying is used to dry the composite material to a moisture content of 5% to 10%, the vacuum drying temperature is controlled between 50°C and 60°C, the drying time is 3 to 6 hours, the temperature is raised to 10°C to 20°C under a vacuum condition with a pressure of 10 to 20 Pa, and the temperature is continued to rise for 6 to 8 hours.

[0017] Furthermore, the powdered flocculant is pulverized by air flow pulverization, the rotation speed of the pulverizing equipment is controlled at 5000 to 10000 rpm, the pulverizing time is 2 to 4 hours, and the particle size uniformity of the obtained powdered flocculant is controlled within the range of ±10 microns.

[0018] Furthermore, the auxiliary agent of the flocculant is partially hydrolyzed polyacrylamide or grafted polyacrylamide, and the process of adding the auxiliary agent includes pre-mixing the auxiliary agent with the powdered flocculant at a ratio of 1% to 10%, and then gradually adding it to the powdered flocculant under a stirring speed of 100 to 300 rpm. The mixing time is controlled at 30 to 60 minutes, and the auxiliary agent is allowed to stand for 12 to 24 hours after mixing to allow the auxiliary agent to fully combine with the surface of the flocculant to form a stable flocculant.

[0019] The present invention provides an application of a chemical flocculant prepared by the preparation process of the chemical flocculant for treating textile printing and dyeing wastewater. The chemical flocculant prepared by the process is applied to the treatment of textile printing and dyeing wastewater to remove suspended matter in the wastewater, reduce the chroma and chemical oxygen demand of the wastewater, and is suitable for the treatment of textile printing and dyeing wastewater containing high-chroma dyes and difficult-to-degrade organic matter.

[0020] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:

[0021] 1. The present invention selects chitosan and starch as main raw materials, performs specific modification treatment on them, combines the specific ratio of aluminum salt and iron salt, and uses appropriate organic acid as an auxiliary, thereby significantly improving the activity and stability of the flocculant. The flocculant in the present invention can effectively remove suspended matter and organic pollutants in wastewater, especially shows excellent treatment effect when treating wastewater with high chroma and difficult-to-degrade organic matter, and is suitable for the efficient treatment of various textile printing and dyeing wastewater.

[0022] 2. The chitosan and starch used in the present invention are both natural degradable materials, which reduce the risk of secondary pollution from chemical agents in the wastewater treatment process; at the same time, by optimizing the temperature, pH value and reaction time in the preparation process, the production cost of the flocculant is reduced, making it more economical and sustainable in practical applications, and further improving the overall efficiency and environmental friendliness of the process. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0027] Example 1

[0028] like Figure 1 As shown, a preparation process of a chemical flocculant for treating textile printing and dyeing wastewater in this embodiment includes the following steps:

[0029] S1. Chitosan and starch are selected as main raw materials. The deacetylation degree of chitosan is 80%. The mass ratio of chitosan to starch is 1:2. The starch is oxidized starch that has been oxidized. The starch is treated with 35% hydrogen peroxide solution at 65°C for 1.5 hours to introduce carboxyl or hydroxyl groups. The treated starch solution is washed, filtered and dried, and then sodium hydroxide solution is added to adjust the pH value to 7.0. It is then dissolved in deionized water and finally used for mixing with chitosan. At the same time, inorganic salts such as aluminum salt and iron salt are added. The mass ratio of aluminum salt to iron salt is 1:1. .5, wherein aluminum sulfate and ferric chloride are mixed in a mass ratio of 1:1.5 and dissolved in deionized water with a concentration of 0.075M, respectively, at 50°C, the stirring time is controlled to 45 minutes, and then the two inorganic salt solutions are mixed and stirred for 25 minutes to form a uniform mixed solution, and then the pH value of the mixed solution is adjusted to 5.2 using a solution pH regulator, and this pH value is maintained until it is mixed with chitosan and starch; and citric acid and lactic acid are added as organic acid substances, and the mass ratio of citric acid to lactic acid is 1:1.5;

[0030] S2, dissolving chitosan and starch separately at 40°C, dissolving chitosan in 0.3M acetic acid solution for 3 hours, filtering the chitosan solution after dissolution to remove insoluble impurities, using continuous stirring at a stirring speed of 200 rpm, and cooling to room temperature after dissolution and standing for 24 hours; dissolving aluminum salt and iron salt in deionized water to prepare a 0.075M solution, dissolving citric acid and lactic acid to prepare a 0.15M solution for standby use;

[0031] S3, the purified chitosan solution was gradually added to the mixed solution of aluminum salt and iron salt under stirring, the reaction temperature was controlled at 50 ° C, the pH value was controlled at 5.0, the pH value was adjusted by adding citric acid and lactic acid solution, the stirring reaction was maintained for 2 hours, the stirring speed was maintained at 300 rpm during the mixing process, and the addition rate was controlled to 4 ml per minute. After the reaction was completed, the reaction solution was continued to be stirred for 45 minutes to form a stable composite material;

[0032] S4, drying the synthesized composite material at 60°C for 4 hours, using vacuum drying to dry the composite material to a moisture content of 8%, the vacuum drying temperature is controlled at 60°C, the drying time is 4 hours, heating to 15°C under a vacuum pressure of 15Pa, and continuing to heat and dry for 7 hours; then pulverizing, the pulverizing process of the powdered flocculant adopts an air flow pulverizing method, the rotation speed of the pulverizing equipment is controlled at 7500 rpm, the pulverizing time is 3 hours, the particle size uniformity of the obtained powdered flocculant is controlled within the range of ±10 microns, and a powdered flocculant with a particle size of 50 microns is obtained; finally, the powdered flocculant is uniformly mixed with a partially hydrolyzed polyacrylamide auxiliary agent with a mass of 5% of its total mass, the auxiliary agent addition process includes pre-mixing the auxiliary agent with the powdered flocculant at a ratio of 5%, and then gradually adding it to the powdered flocculant at a stirring speed of 200 rpm, the mixing time is controlled at 45 minutes, and the mixture is allowed to stand for 18 hours to form a final flocculant.

[0033] Example 2

[0034] A preparation process of a chemical flocculant for treating textile printing and dyeing wastewater, the preparation process comprising the following steps:

[0035] S1. Chitosan and starch are selected as main raw materials. The deacetylation degree of chitosan is 85%. The mass ratio of chitosan to starch is 1:3. The starch is a cationic starch that has been cationized. The starch is treated with a 40% hydrogen peroxide solution at 70°C for 2 hours to introduce hydroxyl groups. The treated starch solution is washed, filtered and dried, and then a sodium hydroxide solution is added to adjust the pH value to 7.5. The solution is then dissolved in deionized water and finally mixed with chitosan. At the same time, inorganic salts such as aluminum salt and iron salt are added. The mass ratio of aluminum salt to iron salt is 1:2, wherein aluminum sulfate and ferric chloride are mixed in a mass ratio of 1:2 and dissolved in deionized water with a concentration of 0.1M, respectively, at 60°C, the stirring time is controlled to 60 minutes, and then the two inorganic salt solutions are mixed and stirred for 30 minutes to form a uniform mixed solution, and then the pH value of the mixed solution is adjusted to 5.5 using a solution pH regulator, and this pH value is maintained until it is mixed with chitosan and starch; and citric acid and lactic acid are added as organic acid substances, and the mass ratio of citric acid to lactic acid is 2:1;

[0036] S2, dissolving chitosan and starch at 50°C, dissolving chitosan in 0.5M acetic acid solution for 2 hours, filtering the chitosan solution after dissolution to remove insoluble impurities, using continuous stirring at a stirring speed of 300 rpm, and cooling to room temperature after dissolution and standing for 24 hours; dissolving aluminum salt and iron salt in deionized water to prepare a 0.1M solution, dissolving citric acid and lactic acid to prepare a 0.2M solution for standby use;

[0037] S3, the purified chitosan solution was gradually added to the mixed solution of aluminum salt and iron salt under stirring, the reaction temperature was controlled at 60 ° C, the pH value was controlled at 6.0, the pH value was adjusted by adding citric acid and lactic acid solution, the stirring reaction was maintained for 3 hours, the stirring speed was maintained at 400 rpm during the mixing process, and the addition rate was controlled to 5 ml per minute. After the reaction was completed, the reaction solution was stirred for 60 minutes to form a stable composite material;

[0038] S4. Dry the synthesized composite material at 70°C for 5 hours, use vacuum drying to dry the composite material to a moisture content of 7%, control the vacuum drying temperature at 55°C, and dry for 6 hours. Heat to 20°C under a vacuum pressure of 20Pa, and continue to heat and dry for 8 hours; then perform a pulverization process. The powdered flocculant is pulverized by an airflow pulverization method. The rotation speed of the pulverizing equipment is controlled at 10,000 rpm. The pulverization time is 4 hours. The particle size uniformity of the obtained powdered flocculant is controlled within the range of ±10 microns, and a powdered flocculant with a particle size of 40 microns is obtained. Finally, the powdered flocculant is uniformly mixed with a grafted polyacrylamide auxiliary agent whose mass is 10% of its total mass. The auxiliary agent addition process includes pre-mixing the auxiliary agent with the powdered flocculant at a ratio of 10%, and then gradually adding it to the powdered flocculant at a stirring speed of 300 rpm. The mixing time is controlled at 60 minutes. After mixing, it is allowed to stand for 24 hours to form a final flocculant.

[0039] By comparing Example 1 and Example 2:

[0040] Flocculation effect:

[0041] Example 1: Since the deacetylation degree of chitosan is low, the oxidized starch used is milder, and the ratio of aluminum salt to iron salt is low, the composite material formed is more stable, and the flocculant shows good sedimentation effect and stability under mild water conditions, and is suitable for the treatment of wastewater with medium pollution degree;

[0042] Example 2: Due to the use of chitosan with a higher degree of deacetylation and cationic starch, combined with a higher proportion of aluminum salt and iron salt, the composite material formed at a higher reaction temperature and pH value has a stronger flocculation ability, can treat wastewater with high chroma and high content of difficult-to-degrade organic matter, and is suitable for the treatment of heavily polluted wastewater.

[0043] Processing efficiency:

[0044] Example 1: Due to the milder treatment conditions, the flocculant of Example 1 has better dispersibility and stability, but the flocculation efficiency may be slightly lower when treating high-concentration pollutants. It is suitable for the treatment of lightly to moderately polluted wastewater;

[0045] Example 2: The high temperature, high pH reaction conditions, and a higher proportion of additives in Example 2 improve the reaction activity and treatment efficiency of the flocculant, can treat high-concentration pollutants more quickly, and is suitable for the rapid treatment of heavily polluted wastewater.

[0046] Environmental protection and economical:

[0047] Example 1: Since the chemical conditions used are relatively mild and the amount of additives used is relatively low, Example 1 is more environmentally friendly and economical, and is suitable for the treatment of conventional industrial wastewater;

[0048] Example 2: Although the chemical conditions of Example 2 are more stringent and the amount of additives used is higher, its stronger processing capacity can cope with highly polluted wastewater, which is more valuable in the highly polluting industrial field. Although the cost is higher, the improvement in efficiency may offset part of the economic cost.

[0049] Embodiment 1 is suitable for general textile printing and dyeing wastewater treatment, and has good environmental protection and economy; while Embodiment 2 is more suitable for treating highly polluted and high-chroma wastewater, and has a stronger treatment effect, but relatively higher cost.

[0050] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0051] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A preparation process of a chemical flocculant for treating textile printing and dyeing wastewater, It is characterized in that The preparation process comprises the following steps: S1, chitosan and starch are selected as main raw materials, the mass ratio of chitosan to starch is 1:1 to 1:3, and inorganic salts such as aluminum salt and iron salt are added, the mass ratio of aluminum salt to iron salt is 1:1 to 1:2, and citric acid and lactic acid are added as organic acid substances, the mass ratio of citric acid to lactic acid is 1:1 to 2:1; S2, dissolving chitosan and starch at 30° C. to 50° C. for 1 to 3 hours, and then purifying them, dissolving aluminum salt and iron salt in deionized water to prepare 0.05M to 0.1M solutions, and dissolving citric acid and lactic acid to prepare 0.1M to 0.2M solutions for later use; S3, gradually adding the purified chitosan solution to the mixed solution of aluminum salt and iron salt under stirring, controlling the reaction temperature at 40°C to 60°C, and the pH value at 4 to 6, adjusting the pH value by adding citric acid and lactic acid solution, and maintaining stirring reaction for 1 to 3 hours to form a stable composite material; S4. Dry the synthesized composite material at 50°C to 70°C for 3 to 5 hours, and then grind it to obtain a powdered flocculant with a particle size of 20 to 80 microns. Finally, evenly mix the powdered flocculant with a polyacrylamide additive whose mass accounts for 1% to 10% of the total mass of the powdered flocculant to prepare a flocculant.

2. The preparation process of a chemical flocculant for treating textile printing and dyeing wastewater according to claim 1, It is characterized in that The deacetylation degree of the chitosan is in the range of 70% to 90%. During the raw material pretreatment process, the chitosan is dissolved in an acetic acid solution, the concentration of the acetic acid solution is 0.1M to 0.5M, the dissolution temperature is controlled between 40°C and 50°C, and the dissolution time is 2 to 4 hours. After the chitosan solution is dissolved, it needs to be filtered to remove insoluble impurities. A continuous stirring method is adopted with a stirring speed of 100 to 300 rpm to promote the complete dissolution of the chitosan. After the solution is dissolved, the solution is cooled to room temperature and left to stand for 24 hours to improve the stability of the solution.

3. The preparation process of a chemical flocculant for treating textile printing and dyeing wastewater according to claim 1, It is characterized in that The starch is oxidized starch that has been oxidized or cationic starch that has been cationized. During the raw material selection process, the starch is treated with a 30% to 40% hydrogen peroxide solution at 60° C. to 70° C. for 1 to 2 hours to introduce carboxyl groups or hydroxyl groups to enhance its hydrophilicity and reactivity. The treated starch solution is washed, filtered and dried, and then a sodium hydroxide solution is added to adjust the pH value to between 6.5 and 7.5, and then dissolved in deionized water for final mixing with chitosan.

4. The preparation process of a chemical flocculant for treating textile printing and dyeing wastewater according to claim 1, It is characterized in that The inorganic salts are aluminum sulfate and ferric chloride. During the preparation of the inorganic salts, aluminum sulfate and ferric chloride are mixed in a mass ratio of 1:1 to 1:2, and dissolved in deionized water with a concentration of 0.05M to 0.1M, respectively. The stirring time is controlled to be 30 to 60 minutes at a temperature of 40°C to 60°C. Then, the two inorganic salt solutions are mixed and stirred for 20 to 30 minutes to form a uniform mixed solution. Subsequently, a solution pH regulator is used to adjust the pH value of the mixed solution to between 5.0 and 5.5, and this pH value is maintained until it is mixed with chitosan and starch.

5. The preparation process of a chemical flocculant for treating textile printing and dyeing wastewater according to claim 1, It is characterized in that In the synthesis step of the composite material, the chitosan solution is slowly added to the mixed solution of aluminum salt and iron salt. During the mixing process, the stirring speed is maintained at 200 to 400 rpm, and the adding speed is controlled to 2 to 5 ml per minute. The reaction temperature is controlled between 50° C. and 60° C. After the reaction is completed, the reaction solution is continuously stirred for 30 to 60 minutes.

6. The preparation process of a chemical flocculant for treating textile printing and dyeing wastewater according to claim 5, It is characterized in that The composite material is dried to a moisture content of 5% to 10% using vacuum drying, the vacuum drying temperature is controlled between 50°C and 60°C, the drying time is 3 to 6 hours, the temperature is raised to 10°C to 20°C under a vacuum condition with a pressure of 10 to 20 Pa, and the temperature is continued to rise for 6 to 8 hours.

7. The preparation process of a chemical flocculant for treating textile printing and dyeing wastewater according to claim 1, It is characterized in that The powdered flocculant is pulverized by air flow pulverization, the rotation speed of the pulverizing equipment is controlled at 5000 to 10000 rpm, the pulverizing time is 2 to 4 hours, and the particle size uniformity of the obtained powdered flocculant is controlled within the range of ±10 microns.

8. The preparation process of a chemical flocculant for treating textile printing and dyeing wastewater according to claim 1, It is characterized in that The auxiliary agent of the flocculant is partially hydrolyzed polyacrylamide or grafted polyacrylamide. The process of adding the auxiliary agent includes premixing the auxiliary agent with the powdered flocculant at a ratio of 1% to 10%, and then gradually adding the auxiliary agent to the powdered flocculant under the condition of a stirring speed of 100 to 300 rpm. The mixing time is controlled at 30 to 60 minutes. After mixing, the auxiliary agent is allowed to stand for 12 to 24 hours to allow the auxiliary agent to fully combine with the surface of the flocculant to form a stable flocculant.

9. Use of the chemical flocculant prepared by the preparation process of the chemical flocculant for treating textile printing and dyeing wastewater according to any one of claims 1 to 8, It is characterized in that The chemical flocculant prepared by the process is applied to the treatment of textile printing and dyeing wastewater, used to remove suspended matter in the wastewater, reduce the chromaticity and chemical oxygen demand of the wastewater, and is suitable for the treatment of textile printing and dyeing wastewater containing high-chromaticity dyes and difficult-to-degrade organic matter.

Citation Information

Patent Citations

  • Inorganic-modified chitosan composite type polymeric flocculant

    CN103121742A

  • Textile printing and dyeing wastewater decolorizing flocculant and preparation method thereof

    CN110902789A

  • Organic composite aluminum sulfate water treatment agent and preparation method thereof

    CN111573801A

  • Preparation method of high-purity aluminum sulfate water treatment flocculant

    CN113336305A

Cited By

  • Coalification wastewater membrane concentrated solution treating agent and preparation method thereof

    CN119977018A

  • Coalification wastewater membrane concentrate treatment agent and preparation method thereof

    CN119977018B